INDONESIAN–PHILIPPINE CO-PRODUCTION MOVIE: FROM RODRIGO DE VILLA TO HOLIDAY IN BALI - Luik, J.E. (Institute of Research and Community Outreach - Petra Christian University, 2009)
The movie industries in Indonesia and the Philippines were facing similar challenge during World War II period. Consequently, post-War period became the period of re-settlement the movie industry with certain efforts. Despite the internal development, expanded the cooperation to the neighbor countries was chosen to strengthen the movie industry. Pioneered by Persari and LVN Pictures, the cooperation expanded to the co-production. The historical literatures and interview to one of the people involved gives the perspective about the cooperation between Indonesia and the Philippine